A water-based rust-bearing polyaniline conversion anticorrosive primer and preparation method thereof
By introducing polyphenol rust converter into polyaniline, a stable complex mesh structure is formed, which solves the problems of incomplete corrosion and loss of rust converter, improves the anticorrosion performance and adhesion, and achieves efficient anticorrosion effect.
Patent Information
- Application Number
- CN202310133230.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-02-17
AI Technical Summary
Existing anticorrosion coatings require complex rust removal treatment before construction, which affects production efficiency and does not completely rust, resulting in reduced or failed anticorrosion functions of the coating, and rust converting agents are prone to falling off, resulting in reduced anticorrosion performance.
Using water-based polyaniline conversion anticorrosion primer, by introducing polyphenol rust converter into polyaniline, the rust converter is fixed to the polyaniline backbone, forming a stable complex mesh structure, enhancing adhesion and preventing rust Converter loss.
It improves the adhesion between the coating and the steel base, enhances the corrosion resistance, avoids the loss of rust converter, and ensures the long-term anti-corrosion effect of the coating.
Smart Images

Figure BDA0004084594030000021 
Figure BDA0004084594030000022 
Figure BDA0004084594030000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rust-coating anticorrosive primers, and in particular relates to a conversion-type rust-coating anticorrosive primer, specifically a water-based rust-coating polyaniline conversion-type anticorrosive primer and a preparation method thereof. Background Art
[0002] The loss caused by metal corrosion to human beings is staggering. The amount of metal loss caused by corrosion is as high as 20-40% of the global metal production every year, with an economic loss of about 1.2 trillion US dollars. Every second, 1.5 tons of steel are corroded. Applying a layer of anti-corrosion coating on the metal surface is the most economical, practical and effective way to prevent metal corrosion. However, when metal is placed in the air and transported, its surface is very easy to produce rust or floating rust. These rusts will directly affect the anti-corrosion effect of the coating. Therefore, before the formal construction of the anti-corrosion coating, a complex rust removal pre-treatment process must be carried out, including the following two situations: First, for the construction of anti-corrosion coating on new steel structures, the steel structure must first be strictly sandblasted and shot blasted to completely remove the floating rust on the surface, requiring it to reach St2.5 level or above; Second, for the anti-corrosion coating that needs to be repaired, the paint film and rust of the original coating need to be thoroughly polished off until the original color of the metal matrix is completely exposed. Surface rust removal of metal substrates is a very complicated task. It not only seriously affects production efficiency, but also has high construction costs and rust dust that harms human health. In addition, it is impossible to perform thorough surface treatment on some large metal structures such as bridges, traffic guardrails and large machinery. More importantly, if the rust on the steel surface is not completely removed, the surface rust will continue to grow, extend and expand from point to surface after painting, causing rust, bulging and cracking on the surface of the paint film, reducing the anti-corrosion function of the paint or directly failing. This is because the rust formed on the metal surface has a loose structure, which not only cannot prevent the penetration of water and oxygen, but also the rust layer exhibits the properties of a porous electrode, which directly affects the dissolved Fe 2+ , dissolved oxygen, and the migration of different substances such as corrosive ions in the rust layer accelerates the corrosion behavior of the metal matrix. Moreover, rust is mostly loose oxides (Fe3O4) or hydroxides (γ-FeOOH or α-FeOOH) of iron, which have a higher potential than iron and can promote the corrosion reaction of metals. Pure γ-FeOOH and α-FeOOH rust films act as cathode reactions in the electrochemical process, promoting the corrosion of steel under the rust film. Among them, the α-FeOOH rust film has a loose porous structure and a high cathode reaction activity. The corrosion process is controlled by the diffusion process of the electrolyte in the porous film, and the corrosion is aggravated. Therefore, it is very necessary to develop a new type of rust-resistant coating that can be directly applied to the surface of rusted steel.
[0003] Conversion type rust-resistant primer is a reactive anti-corrosion coating. Its mechanism is that the primer contains a chelating agent that can react with rust to increase the adhesion between the base and the coating. Phosphoric acid and tannic acid have been widely studied as rust conversion agent components in the research of conversion type rust-resistant primer. However, these two acids are small molecular acids. After forming chelates (salts) with rust, they are very easy to be released in the corrosive medium. Once they fall off from the coating, coating defects will be formed, resulting in accelerated anti-corrosion performance. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a water-based rust-bearing polyaniline conversion anticorrosive primer and a preparation method thereof. The anticorrosive primer provided by the present invention has good anticorrosive performance and adhesion.
[0005] The present invention provides a water-based rust-bearing polyaniline conversion anticorrosive primer, which comprises, in parts by weight:
[0006]
[0007] Preferably, the water-based polyaniline has a structure of Formula I:
[0008]
[0009] In Formula I,
[0010]
[0011] 0≤y≤1, 1≤n≤100, 1≤m≤9.
[0012] Preferably, the penetrant is selected from one or more of methanol, isopropanol and n-butanol.
[0013] Preferably, the pigments and fillers are selected from three or four of talc, titanium dioxide, sericite, glass flakes, precipitated barium sulfate, and calcium carbonate.
[0014] The present invention provides a method for preparing the water-based rust-bearing polyaniline conversion anticorrosive primer described in the above technical solution, comprising:
[0015] The water, dispersant, defoamer and pigment are first mixed to obtain a slurry;
[0016] Grinding the slurry to obtain a color paste;
[0017] The color paste, acrylic resin, water-based polyaniline, penetrant and leveling agent are mixed for a second time and then filtered to obtain a water-based rust-bearing polyaniline conversion anti-corrosion primer.
[0018] Preferably, the first mixing is dispersed under stirring, the stirring speed is 750-850 rpm, and the dispersion time is 15-30 min;
[0019] The second mixing is performed under stirring conditions; the stirring speed is 350-450 rpm, and the stirring time is 20-40 min.
[0020] Preferably, the grinding is performed to a fineness of 15 to 25 μm.
[0021] Preferably, the preparation method of the water-based polyaniline comprises:
[0022] The intrinsic polyaniline, deionized water and a polyphenol rust conversion agent are subjected to a first reaction to obtain a reaction product;
[0023] The reaction product and the dopant are subjected to a second reaction to obtain waterborne polyaniline.
[0024] Preferably, the polyphenol rust conversion agent is selected from tannic acid and gallic acid.
[0025] Preferably, the dopant is an aqueous phosphate dopant containing an ethoxy group.
[0026] The invention provides a water-based polyaniline with a novel structure, wherein a rust converter containing a polyphenol structure is fixed on the main chain structure of the polyaniline, thereby preventing the loss of the rust converter, ensuring the anti-corrosion effect, and enhancing the adhesion between the coating and the steel base. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the SEM image of the water-based polyaniline prepared in Example 1;
[0028] Figure 2 This is the SEM image of the water-based polyaniline prepared in Example 2. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a water-based rust-bearing polyaniline conversion anticorrosive primer, which comprises, in parts by weight:
[0031]
[0032] In the present invention, the weight proportion of the acrylic resin is preferably 55 to 80 parts, more preferably 60 to 75 parts, and most preferably 65 to 70 parts.
[0033] In the present invention, the acrylic resin is preferably a water-based acrylic resin, and more preferably is selected from one or more of Dow PRIMALAS-8508, PRIMAL B-959, BASF JoncrylFLX 5020, and AcronalS 400Fap.
[0034] In the present invention, the weight proportion of the polyaniline is preferably 35 to 40 parts, more preferably 36 to 38 parts.
[0035] In the present invention, the aqueous polyaniline preferably has a structure of formula I:
[0036]
[0037] In Formula I,
[0038]
[0039] 0≤y≤1, 1≤n≤300, 1≤m≤9.
[0040] In the present invention, y is preferably 0.2-0.8, more preferably 0.4-0.6, most preferably 0.5; n is preferably 5-200, more preferably 10-180, more preferably 20-170, more preferably 30-160, most preferably 40-150; m is preferably 2-8, more preferably 3-7, most preferably 4-6.
[0041] In the present invention, the method for preparing the water-based polyaniline preferably comprises:
[0042] The intrinsic polyaniline, water and a polyphenol rust conversion agent are subjected to a first reaction to obtain a reaction product;
[0043] The reaction product and the dopant are subjected to a second reaction to obtain waterborne polyaniline.
[0044] In the present invention, the intrinsic polyaniline is preferably an intrinsic polyaniline powder; the Mn (number average molecular weight) of the intrinsic polyaniline powder is preferably 28000-76000Da, more preferably 30000-70000Da, more preferably 40000-60000Da, most preferably 50000Da; the particle size of the intrinsic polyaniline powder is preferably 35-50 microns, more preferably 40-45 microns, most preferably 42-43 microns.
[0045] In the present invention, the water is preferably deionized water.
[0046] In the present invention, the polyphenol rust conversion agent is preferably selected from one of tannic acid and gallic acid.
[0047] In the present invention, the mass ratio of the intrinsic polyaniline, water and polyphenol rust conversion agent is preferably (60-110): (2100-3800): (45-70), more preferably (70-100): (2500-3500): (50-60), and most preferably (80-90): (2800-3200): 55.
[0048] In the present invention, the first reaction is preferably carried out under stirring; the temperature of the first reaction is preferably 80-100°C, more preferably 85-95°C, most preferably 90°C; the time of the first reaction is preferably 2-4 hours, more preferably 3 hours.
[0049] In the present invention, the dopant is preferably an aqueous dopant, more preferably an aqueous dopant containing ethoxy groups, and most preferably a phosphate containing ethoxy repeating units, which can be prepared according to the method of Geng et al. (Polymer, 1999, 40, 5723-5727).
[0050] In the present invention, the mass ratio of the polyaniline to the dopant is preferably (60-110):(55-135), more preferably (70-100):(60-130), more preferably (80-90):(70-120), and most preferably 85:(80-110).
[0051] In the present invention, the second reaction is preferably carried out under stirring, the temperature of the second reaction is preferably 25-35°C, more preferably 28-32°C, most preferably 30°C; the time of the second reaction is preferably 0.5-2 hours, more preferably 1-1.5 hours.
[0052] In the present invention, the weight proportion of the penetrant is preferably 9 to 14 parts, more preferably 10 to 13 parts, and most preferably 11 to 12 parts.
[0053] In the present invention, the penetrant is preferably selected from one or more of methanol, isopropanol, and n-butanol.
[0054] In the present invention, the weight proportion of the pigment and filler is preferably 15 to 25 parts, more preferably 18 to 22 parts, and most preferably 20 parts.
[0055] In the present invention, the pigments and fillers are preferably selected from three or four of talc, titanium dioxide, sericite, glass flakes, precipitated barium sulfate, and calcium carbonate.
[0056] In the present invention, the weight proportion of the leveling agent is preferably 0.5 to 2.5 parts, more preferably 1 to 2 parts, and most preferably 1.5 parts.
[0057] In the present invention, the leveling agent is preferably a water-based leveling agent, more preferably one or more selected from BYK-306, BYK-307, BYK-301, BYK-302, BYK-333, BYK-325, BYK-341, BYK-345, BYK-346, BYK-370, BYK-348, and BYK-375.
[0058] In the present invention, the weight proportion of the defoaming agent is preferably 1 to 3 parts, more preferably 1.5 to 2.5 parts, and most preferably 2 parts.
[0059] In the present invention, the defoamer is preferably an aqueous defoamer, more preferably one or more selected from BYK-031, BYK-027, BYK-032, BYK-021, BYK-045, BYK-033, BYK-022, BYK-034, BYK-023, BYK-035, BYK-036, BYK-037, BYK-026, and BYK-011.
[0060] In the present invention, the dispersant is preferably 1 to 2 parts, more preferably 1.5 parts.
[0061] In the present invention, the dispersant is preferably an aqueous dispersant, more preferably one or more selected from DISPERBYK-180, DISPERBYK-181, DISPERBYK-182, DISPERBYK-184, and DISPERBYK-190.
[0062] In the present invention, the weight proportion of water is preferably 18 to 22 parts, more preferably 20 parts.
[0063] In the present invention, the water is preferably deionized water.
[0064] The present invention provides a method for preparing the water-based rust-bearing polyaniline conversion anticorrosive primer described in the above technical solution, comprising:
[0065] The water, dispersant, defoamer and pigment are first mixed to obtain a slurry;
[0066] Grinding the slurry to obtain a color paste;
[0067] The color paste, acrylic resin, water-based polyaniline, penetrant and leveling agent are mixed for a second time and then filtered to obtain a water-based rust-bearing polyaniline conversion anti-corrosion primer.
[0068] In the present invention, the first mixing is preferably dispersed under stirring, and the stirring speed is preferably 750-850 rpm, more preferably 780-820 rpm, and most preferably 800 rpm; the dispersion time is preferably 15-30 min, more preferably 20-25 min.
[0069] In the present aspect, the grinding is preferably to send the slurry to a sand mill; the grinding is preferably to a fineness of 15 to 25 μm, more preferably 18 to 22 μm, and most preferably 20 μm.
[0070] In the present invention, the second mixing is preferably carried out in a dispersion kettle, and the second mixing is preferably carried out under stirring; the stirring speed is preferably 350-450 rpm, more preferably 380-420 rpm, and most preferably 400 rpm; the stirring time is preferably 20-40 min, more preferably 25-35 min, and most preferably 30 min.
[0071] In the present invention, the filtration is preferably carried out by nylon cloth filtration; the mesh number of the nylon cloth is preferably 80 to 120 meshes, more preferably 100 meshes.
[0072] In the present invention, the rust conversion mechanism of waterborne polyaniline is as follows: the oxygen on the hydroxyl group in the polyphenol structure of the side chain of waterborne polyaniline is replaced by O - With Fe in rust Fe3O4 3+ The complexation reaction (Formula II to Formula V) occurs to form a stable complex network structure with good adhesion. It can be tightly combined with the surface of the iron matrix, which not only plays a good anti-corrosion role, but also can solve the adhesion problem caused by rust. The water-based phosphate ester with a side chain structure has two functions. The first function is to form a phosphating film with rust, which has excellent anti-corrosion performance. At the same time, the phosphate ester can remove the deep Fe in the rust. 3+ The rust is dissolved and completely converted into a chelate coating with better adhesion to the steel base; and polyaniline not only plays an anti-corrosion role in the system, but also acts as a corrosion inhibitor.
[0073]
[0074]
[0075]
[0076] Example 1 Synthesis of water-based polyaniline
[0077] 60 g of polyaniline (Mn=28000 Da, particle size 35 μm, y=0.5) powder, 2100 g of deionized water and 45 g of tannic acid were added to a reactor, the temperature was raised to 80° C., stirred for 4 hours, then the temperature was lowered to 25° C., 55 g of a monophosphate aqueous dopant containing one ethoxy repeating unit (m=1) was added, stirred for 2 hours, and an aqueous polyaniline dispersion of formula VI was obtained.
[0078]
[0079] The aqueous polyaniline particles prepared in Example 1 were tested. The aqueous polyaniline prepared in Example 1 had Mn=32500Da, PDI=2.58, Zeta potential of aqueous polyaniline emulsion: 48mV, and particle size of aqueous polyaniline was 1-1.5 microns. Figure 1 shown.
[0080] Mn and PDI test of waterborne polyaniline:
[0081] The Mn and PDI of aqueous polyaniline were completed on a gel permeation chromatography (GPC) instrument. Polyaniline was dissolved in N-methylpyrrolidone to make 1 mg / ml, and N-methylpyrrolidone was used as the eluent for molecular weight testing.
[0082] Zeta potential test of water-based polyaniline emulsion:
[0083] Zeta potential was measured on a Malvern-ZS90 dynamic light scattering (DLS) instrument at 25 °C after the emulsion was transferred into a folded capillary cell.
[0084] Example 2 Synthesis of water-based polyaniline
[0085] 110 g of polyaniline (Mn=76000 Da, particle size 45 μm, y=0.6) powder, 3800 g of deionized water and 70 g of gallic acid were added to a reactor, the temperature was raised to 100° C., stirred for 2 hours, then the temperature was lowered to 35° C., 135 g of a monophosphate aqueous dopant containing nine ethoxy repeating units (m=9) was added, stirred for 0.5 hour, and an aqueous polyaniline dispersion of formula VII was obtained.
[0086]
[0087] The aqueous polyaniline prepared in Example 2 has Mn=87500Da, PDI=3.18, Zeta potential of aqueous polyaniline emulsion: 51mV, and particle size of aqueous polyaniline is 0.8-1.2 microns. Figure 2 shown.
[0088] Example 3 Synthesis of water-based polyaniline
[0089] 80 g of polyaniline (Mn=42000 Da, particle size 42 μm, y=0.5) powder, 2500 g of deionized water and 55 g of tannic acid were added to a reactor, the temperature was raised to 90° C., stirred for 3 hours, then the temperature was lowered to 30° C., 60 g of a diphosphate aqueous dopant containing an ethoxy repeating unit (m=1) was added, stirred for 1 hour, and an aqueous polyaniline dispersion of formula VIII was obtained.
[0090]
[0091] The aqueous polyaniline prepared in Example 3 has Mn=51800 Da, PDI=3.85, Zeta potential of aqueous polyaniline emulsion: 42 mV, and particle size of aqueous polyaniline is 1.3-1.8 μm.
[0092] Example 4 Synthesis of water-based polyaniline
[0093] 100 g of polyaniline (Mn=56000 Da, particle size 47 μm, y=0.55) powder, 3500 g of deionized water and 60 g of gallic acid were added to a reactor, the temperature was raised to 95° C., stirred for 3.5 hours, then the temperature was lowered to 32° C., 115 g of a monophosphate aqueous dopant (m=5) containing five ethoxy repeating units was added, stirred for 1.5 hours, and an aqueous polyaniline dispersion of formula IX was obtained.
[0094]
[0095] The aqueous polyaniline prepared in Example 4 has Mn=71520 Da, PDI=2.91, the Zeta potential of the aqueous polyaniline emulsion is 45 mV, and the particle size of the aqueous polyaniline is 0.6-0.75 μm.
[0096] Example 5 Synthesis of water-based polyaniline
[0097] 95 g of polyaniline (Mn=35800 Da, particle size 37 μm, y=0.6) powder, 3100 g of deionized water and 62 g of tannic acid were added to a reactor, the temperature was raised to 88° C., stirred for 2.5 hours, then the temperature was lowered to 30° C., 105 g of a monophosphate aqueous dopant (m=2) containing two ethoxy repeating units was added, stirred for 1 hour, and an aqueous polyaniline dispersion of formula X was obtained.
[0098]
[0099] The aqueous polyaniline prepared in Example 5 has Mn=42150 Da, PDI=4.15, Zeta potential of aqueous polyaniline emulsion: 40 mV, and particle size of aqueous polyaniline is 1.5-1.9 microns.
[0100] Comparative Example 1 Synthesis of water-based polyaniline
[0101] Aqueous polyaniline was prepared according to the method of Example 1, except that tannic acid was not added.
[0102] Comparative Example 2 Synthesis of water-based polyaniline
[0103] Aqueous polyaniline was prepared according to the method of Example 2, except that gallic acid was not added.
[0104] Example 6 Preparation of water-based rust-resistant polyaniline anticorrosive coating
[0105] According to the raw material ratio shown in Table 1, a water-based rust conversion primer was prepared according to the following method. The water-based polyaniline prepared in Examples 1 to 5, Comparative Example 1 and Comparative Example 2 was mixed with other raw materials to prepare different rust conversion primers, which were marked as primers PAN1 to PAN5, DB1 and DB2 respectively;
[0106] The first step is to add deionized water, dispersant, defoamer and pigment filler into the dispersion kettle respectively, disperse at a speed of 750-850 rpm for 15-30 minutes to form a slurry, and then pump the slurry to a sand mill and grind it to a fineness of less than 20 μm to prepare a color paste.
[0107] In the second step, the color paste prepared in the first step is pumped into the dispersion kettle, and the water-based resin emulsion, water-based polyaniline, penetrant and water-based leveling agent are added. The mixture is stirred at a speed of 350-450 rpm for 30 minutes, and filtered through a 100-mesh nylon cloth to obtain a water-based rust-resistant polyaniline conversion anti-corrosion primer.
[0108] Table 1 Ratio of raw materials for preparing water-based rust-resistant polyaniline conversion anticorrosive primer
[0109]
[0110] Performance Testing
[0111] Adhesion test: The loose rust on the surface of the rusty steel plate was polished with sandpaper to remove the surface rust, and then the water-based rust conversion primer prepared in Example 6 was applied (the dry film thickness of the paint film was 70±5 μm). After natural drying for 2 hours, a layer of two-component epoxy anticorrosive primer was applied (the epoxy resin was bisphenol A epoxy resin, selected from 6101 epoxy resin of Jiangsu Sanmu Company, and the curing agent was cashew nut oil-modified phenolic amine, selected from NX-2015 of Cardolite). The dry film thickness of the epoxy anticorrosive primer was controlled at 170±10 μm. After 72 hours of testing, the adhesion test was performed.
[0112] Water resistance, impact resistance, bending test and 3% NaCl solution test: The water-based conversion primer was applied on the rust-free tinplate (thickness 150±10 μm), and relevant performance tests were performed after 24 hours.
[0113] The test results are as follows:
[0114]
[0115] The invention provides a water-based polyaniline with a novel structure, wherein a rust converter containing a polyphenol structure is fixed on the main chain structure of the polyaniline, thereby preventing the loss of the rust converter, ensuring the anti-corrosion effect, and enhancing the adhesion between the coating and the steel base.
[0116] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.
Claims
1. A water-based rust-resistant polyaniline conversion anticorrosive primer, comprising, by weight: The preparation method of the water-based polyaniline comprises: The polyaniline, water and a polyphenol rust conversion agent are subjected to a first reaction to obtain a reaction product; the reaction product and a dopant are subjected to a second reaction to obtain waterborne polyaniline; The polyphenol rust conversion agent is selected from one of tannic acid and gallic acid; The dopant is a phosphate containing ethoxy repeating units; The water-based polyaniline has a structure of formula I: In Formula I, 0≤y<1, 1≤n≤100, 1≤m≤9.
2. The water-based rust-bearing polyaniline conversion anticorrosive primer according to claim 1, characterized in that: The penetrant is selected from one or more of methanol, isopropanol and n-butanol.
3. The water-based rust-bearing polyaniline conversion anticorrosive primer according to claim 1, characterized in that: The pigments and fillers are selected from three or four of talc, titanium dioxide, sericite, glass flakes, precipitated barium sulfate and calcium carbonate.
4. A method for preparing the water-based rust-bearing polyaniline conversion anticorrosive primer according to claim 1, comprising: The water, dispersant, defoamer and pigment are first mixed to obtain a slurry; Grinding the slurry to obtain a color paste; The color paste, acrylic resin, water-based polyaniline, penetrant and leveling agent are mixed for a second time and then filtered to obtain a water-based rust-bearing polyaniline conversion anti-corrosion primer.
5. The method according to claim 4, characterized in that The first mixing is dispersed under stirring, the stirring speed is 750-850 rpm, and the dispersing time is 15-30 min; The second mixing is performed under stirring conditions; the stirring speed is 350-450 rpm, and the stirring time is 20-40 min.
6. The method according to claim 4, characterized in that: The grinding process is performed to a fineness of 15 to 25 μm.
